2019
DOI: 10.3389/fmicb.2019.01924
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infection in Pregnancy on Placental Vascular Development and Adverse Birth Outcomes

Abstract: Healthy fetal development is dependent on nutrient and oxygen transfer via the placenta. Optimal growth and function of placental vasculature is therefore essential to support in utero development. Vasculogenesis, the de novo formation of blood vessels, and angiogenesis, the branching and remodeling of existing vasculature, mediate the development and maturation of placental villi, which form the materno-fetal interface. Several lines of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 145 publications
(205 reference statements)
6
75
0
4
Order By: Relevance
“…We found a significantly rising incidence of low birth weight babies among BMI more than or equal to 35mothers 83.3%. which is similar to Takai et al, 2017 [15] results which may be due to dysregulation of proinflammatory cytokines as well as increased risk of infection in obese and overweight individuals as they will lead to reduced placental surface area and also their vasculature with consequent uteroplacental insufficiency [16] In our study, we found more incidence of IUGR and NICU admissions in the BMI group more than or equal to 35, which is like Shah PM et al 2018 results [17] .…”
Section: Discussionsupporting
confidence: 90%
“…We found a significantly rising incidence of low birth weight babies among BMI more than or equal to 35mothers 83.3%. which is similar to Takai et al, 2017 [15] results which may be due to dysregulation of proinflammatory cytokines as well as increased risk of infection in obese and overweight individuals as they will lead to reduced placental surface area and also their vasculature with consequent uteroplacental insufficiency [16] In our study, we found more incidence of IUGR and NICU admissions in the BMI group more than or equal to 35, which is like Shah PM et al 2018 results [17] .…”
Section: Discussionsupporting
confidence: 90%
“…Early in pregnancy, the uterine spiral arteries are structurally converted from small diameter arteries into low-resistance large diameter vessels by interaction with the fetal placental extravillous trophoblasts that invade the myometrium and the spiral arteries [159]. Some chemicals have been shown to interfere with vascular remodeling and development of the placenta, thereby impairing oxygen and nutrient delivery to the fetus and ultimately increasing the risk for adverse pregnancy outcomes (reviewed in [160,161]). Several epidemiological studies have found that components of air pollution, including PM with 2.5 μm or less in diameter (PM 2.5 ) , were associated with increased risk of pregnancy-induced hypertensive disorders [2].…”
Section: Nm Interference With Vascular Signaling and Utero-placental mentioning
confidence: 99%
“…Whether the impact from periodontal infection influences or explicates a direct effect is uncertain but suggests a potentially damaging interaction between periodontitis and preterm delivery (PTD) [23]. From the empirical findings, a clear interest focused on the placental inflammation has emerged [1], [4], [25], [26], [27], [28], [29]. Central relationship between the periodontal disease and preterm birth (PTB) is due to an inflammatory response system responding to signal from bacterial invasion [30], [31].…”
Section: Periodontal Disease and Oral Microbiomementioning
confidence: 99%
“…Interestingly, a similarity between placental and oral microbiome was found to be essential to describe as coherent a hypothesis of relationship between oral dysbiosis and pregnancy poor outcomes [32], [33], [34], [35], [36], [37]. This hypothesis is referred to an activate inflammatory signaling pathways stimulated by periodontal damage, or direct dissemination of periodontal pathogens through hematogenous spread from the oral cavity [18], [21], [27], [35], but they do not fully explain such behaviors, suggesting that other mechanisms and factors might play a key role in determining the link [22], [23], [24], [25]. Fusobacterium nucleatum (FN) is an opportunistic commensal Gram-negative anaerobe microorganism ubiquitous to the oral cavity, one of the most abundant pathogens implicated in severe periodontal disease [18], [38], [39], [40], [41], [42], [43], [44], [45], [46].…”
Section: Periodontal Disease and Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation